The double-edged sword effects of leader perfectionism on employees' job performance: the moderating role of self-efficacy - Lingjiang Zhao; Haishen Huang (Frontiers in Psychology)
The pursuit of perfection has become a common job requirement for modern organizations against the backdrop of increasingly fierce market competition. Drawing upon appraisal theory of emotion, we develop and test a model delineating the paradoxical role that leader perfectionism plays in predicting employee's job performance. Specifically, we propose that leader perfectionism improves job performance through increased harmonious work passion and simultaneously hinders it through enhanced performance pressure. We further propose self-efficacy as boundary condition, such that the positive path through harmonious work passion is stronger and the negative path through performance pressure is weaker for individuals with higher (vs. lower) levels of self-efficacy. Finding from a three-wave and multisource field study provides support for our hypothesized predictions. Finally, we discuss theoretical and practical implications of this study.